2019
DOI: 10.3171/2017.12.jns172188
|View full text |Cite
|
Sign up to set email alerts
|

Regression after subtotal resection of an optic pathway glioma in an adult without adjuvant therapy: case report

Abstract: Optic pathway gliomas (OPGs) are relatively common and benign lesions in children; however, in adults these lesions are nearly always malignant and hold a very poor prognosis. In this report the authors present the case of an adult patient with a benign OPG who underwent subtotal resection without adjuvant therapy and has had no tumor progression for more than 20 years. A 50-year-old woman presented with a 2-year history of personality changes, weight gain, and a few months of visual disturbances. Ophthalmolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…9,28 The best treatment in adult patients also remains uncertain, as there is evidence that its presence in older individuals can lead to a worse prognosis. 33…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,28 The best treatment in adult patients also remains uncertain, as there is evidence that its presence in older individuals can lead to a worse prognosis. 33…”
Section: Discussionmentioning
confidence: 99%
“…The best course of treatment in adult patients remains unclear, but it is usually approached differently than in children, given the malignant characteristic that these tumors usually present in this age group. 33 Wabbels et al 34 report in their study that loss of unilateral visual acuity is the presenting symptom in 70% of adult cases and bilateral in 30%. Headaches, ophthalmoplegia, and neurologic deficits, including hemiparesis, are other signs and symptoms associated with tumor presence.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…To our knowledge, there have been only nine documented cases of low-grade optic pathway gliomas in adults in the past few years. [17,16] The recent case study by Hidalgo et al demonstrated that an adult patient with low-grade optic pathway glioma who received no adjuvant therapy after STR could survive more than 20 years without tumor progression. [16] In another study that included limited 14 children with optic chiasmatic-hypothalamic gliomas, no signi cant differences were observed regarding the volume change of tumors treated or not treated with chemotherapy.…”
Section: Factors Associated With Survival and Tumor Managementmentioning
confidence: 99%
“…[17,16] The recent case study by Hidalgo et al demonstrated that an adult patient with low-grade optic pathway glioma who received no adjuvant therapy after STR could survive more than 20 years without tumor progression. [16] In another study that included limited 14 children with optic chiasmatic-hypothalamic gliomas, no signi cant differences were observed regarding the volume change of tumors treated or not treated with chemotherapy. [32] The critical nding in our study shows that both adjuvant RT and chemotherapy may have potentially adverse effects on survival in adult patients with low-grade ONGs.…”
Section: Factors Associated With Survival and Tumor Managementmentioning
confidence: 99%
See 1 more Smart Citation